Temperature and humidity measurement using an off-the-shelf MEMS sensor: Beyond arduino's playground - De Lucena, Samuel E. [UNESP]; Sampaio, Daniel J. B. S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In this work an off-the-shelf, modern, integrated temperature, pressure and humidity sensor was interfaced to a PIC18F4550, a popular 8-bit microcontroller. A bit-banging SPI protocol was implemented. The SPI clock was set to 10-kHz to allow for relatively long distance between the microcontroller's board and the sensor's board. Temperature and humidity data stemming from two BME280 sensors were compared with data supplied by a commercial handheld temperature and humidity measuring instrument.
Keywords: bit-banging; embedded systems; humidity measurement; MEMS sensors; microcontroller; serial communications; SPI protocol; temperature measurement; weather station